Judt, Tony. Algo va mal. Madrid, España, Taurus, 2010 (220 p.). ISBN 9788430607969 - Sagredo Mazuela, Omar (Estudios Avanzados, 2013)
Judt, Tony. Algo va mal. Madrid, España, Taurus, 2010 (220 p.). ISBN 9788430607969